Improving the Performance of Digital Marketing in the Handicraft Industry Through the Implementation of Digital Marketing Strategies - Nurdima, Fildzah; Prasetyo, Johan Hendri (STIE Tri Bhakti, 2026)
The development of digital technology has driven significant changes in marketing activities, especially for Micro, Small, and Medium Enterprises (MSMEs) in the creative industry sector. Although digital opportunities are expanding, many handicraft businesses have not optimized their digital marketing strategies effectively, resulting in low brand awareness and sales performance. This study aims to analyze the implementation of digital marketing strategies in improving marketing performance and brand awareness at Arna Decor, a wood MDF wall decoration business. The method used is a qualitative descriptive approach with a case study. Data was collected through direct observation of digital marketing activities on Instagram, TikTok, Shopee, Tokopedia, and TikTok Shop, documentation of social media insights and sales reports, literature studies, and supporting quantitative analysis using ROAS and ROI indicators. The results of the study show a significant increase after the optimization of digital marketing strategies. Instagram profile activity increased by 155.6% in three months, while TikTok content views increased by 11.3% in 60 days. Shopee ad performance improved with an ROAS of 4.77, where advertising costs of IDR 3,600,000 generated sales of IDR 17,200,000 with a total of 497 products sold. Advertisements on Tokopedia and TikTok Shop recorded an ROI of 1.87. The affiliate program also made a positive contribution with sales of IDR 2,500,000 on Shopee and IDR 961,700 on TikTok Shop. Thus, the implementation of structured, consistent, and data-driven digital marketing has proven effective in increasing brand awareness, engagement, and sales revenue for Arna Decor, while also strengthening the competitiveness of SMEs in the handicraft industry